2020
DOI: 10.1590/1413-82712020250306
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health, Cognition and Academic Performance in the 1st Year of Elementary Education

Abstract: The study investigated 1) relationships and explanatory models of mental health indicators from cognitive abilities and 2) relationships between mental health indicators and academic performance one year later. Participants were 86 children, students of the 1st year of Elementary Education, evaluated in intelligence, inhibitory control (IC) and language. Parents and teachers completed the Strengths and Difficulties Questionnaire (SDQ). One year later, the children were re-evaluated in word recognition (WR) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
(63 reference statements)
0
2
0
Order By: Relevance
“…By comparison, there was a weaker association between the Strengths and Difficulties Questionnaire (SDQ) and the SAT. This may partly be because SDQ is a caregiver-reported tool, although caregiverreported and teacher-reported SDQ were associated with academic scores among children in Brazil 62 .…”
Section: Discussionmentioning
confidence: 98%
“…By comparison, there was a weaker association between the Strengths and Difficulties Questionnaire (SDQ) and the SAT. This may partly be because SDQ is a caregiver-reported tool, although caregiverreported and teacher-reported SDQ were associated with academic scores among children in Brazil 62 .…”
Section: Discussionmentioning
confidence: 98%
“…By comparison, there was no association between the Strengths and Difficulties Questionnaire (SDQ) and the SAT. This may partly be because SDQ is a caregiver-reported tool, although caregiver-reported and teacher-reported SDQ were associated with academic scores among children in Brazil [ 71 ]. A recent follow-up of the MAL-ED cohort showed that socioeconomic status was associated with cognitive scores at 5 years [ 72 ]; our study also found a trend towards increasing MPI with a rise in socioeconomic scale.…”
Section: Discussionmentioning
confidence: 99%
“…O desenvolvimento integral da criança demanda a estimulação de aspectos para além das competências acadêmicas, devendo incluir habilidades cognitivas, emocionais, sociais e físicas (Altun, 2018;Dias & Seabra, 2020). Uma das habilidades que figura entre aquelas que são necessárias ao desenvolvimento infantil saudável é a autorregulação (AR) (Robson et al, 2020).…”
Section: Introductionunclassified